CLASSICAL LITERATURE GENRES IN THE WORK OF NODIRA AFAKOVA - Kamolova Mahliyo Iskandar qizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the creative heritage of Nodira Afokova, a prominent representative of Uzbek literature, from the perspective of classical literary genres. The poet and prose writer's poetic, lyrical-epic and prose works study the unique interpretation of traditional genres - ghazal, muhammas, rubai, qasida and doston. The article presents scientific conclusions on how Nodira combined classical literary traditions with modern aesthetic thinking. The research uses literary analysis, comparative-typological and historical-genetic methods.